Analisis hubungan antara pengetahuan, sikap, dan, tindakan dengan kesiapsiagaan banjir pada masyarakat di Kecamatan Mandolang, Minahasa - Lamandasa, Ghervin Imanuel Olanis; Wariki, Windy Mariane Virenia; Porajow, Zwingly Christian Jefferson Gerard (Jurnal Kedokteran Komunitas dan Tropik, 2025)
Background: Floods occur frequently in Indonesia and pose substantial risks to affected communities. Community preparedness is shaped by levels of knowledge, attitudes, and practices related to disaster risk reduction. Aim: This study aimed to examine the relationship between knowledge, attitudes, and practices and flood preparedness among residents of Tateli Tiga Village. Methods: A quantitative cross-sectional design was employed, involving 97 respondents selected through proportional quota sampling. Data were collected using a validated and reliable questionnaire. Statistical analysis was conducted using the Chi-square test or Fisher’s exact test, as appropriate. Result: The majority of respondents demonstrated good knowledge (82.5%), positive attitudes (78.3%), good practices (86.6%), and adequate flood preparedness (52.6%). A significant association was identified between knowledge and flood preparedness (p = 0.035; OR = 3.247). No significant associations were observed between attitudes (p = 0.070) or practices (p = 0.487) and preparedness. Conclusion: Knowledge was significantly associated with community flood preparedness, whereas attitudes and practices were not.